Noninvasive Prenatal Testing of Methylmalonic Acidemia cblC Type Using the cSMART Assay for MMACHC Gene Mutations - Lv, Weigang; Liang, Lili; Chen, Xin; Li, Zhuo; Liang, Desheng; Zhu, Huimin; Teng, Yanling; Wu, Weijuan; Wu, Lingqian; Han, Lianshu (Frontiers in Genetics, 2022)
Noninvasive prenatal testing (NIPT) for monogenic disorders has been developed in recent years, however, there are still significant technical and analytical challenges for clinic use. We investigated the clinical feasibility of NIPT for methylmalonic acidemia cblC type (cblC type MMA) using our circulating single-molecule amplification and resequencing technology (cSMART). Trios molecular diagnosis was performed in 29 cblC type MMA-affected children and their parents by traditional Sanger sequencing. In the second pregnancy, invasive prenatal diagnosis (IPD) of the pathogenic MMACHC gene was used to determine fetal genotypes, and NIPT was performed using a novel MMACHC gene-specific cSMART assay. Maternal-fetal genotypes were deduced based on the mutation ratio in maternal plasma DNA. Concordance of fetal genotypes between IPD and NIPT and the sensitivity and specificity of NIPT were determined. After removing two cases with low P value or reads, the concordance ratio for NIPT and IPD was 100.00% (27/27), and the sensitivity and specificity were 100.00% (54.07% to 100.00%) and 100.00% (83.89% to 100.00%), respectively. This study demonstrates that NIPT using the cSMART assay for cblC type MMA was accurate in detecting fetal genotypes. cSMART has a potential clinical application as a prenatal diagnosis and screening tool for carrier and low-risk couplies of cblC type MMA and other monogenic diseases.